A Potential Amphiprotic Sponge with a Controlled Release Characteristic of Protons on Demand for Oil/Water Separation and Acid/Base Neutralization. Issue 9 (28th March 2019) - Kaang, Byung Kwon; Lee, Yo Seph; Han, Nara; Choi, Won San
Abstract: Ultralight sponges with the ability to release protons on demand, namely, superhydrophobic melamine formaldehyde sponges (SHpho‐MFSs), which are characterized as being safe‐to‐handle, convenient‐to‐use, easy‐to‐store, easy‐to‐carry, and easy‐to‐collect, are switched from superhydrophilic MFSs (SHphi‐MFSs) by a one‐step ultrasound treatment at a low pH. The wettability of the SHphi‐MFS is completely switched from the outside to the inside of the MFS. After wettability switching is achieved, the SHpho‐MFS that is prewetted with water and oil is able to selectively separate both water and oil, respectively. A compressed SHpho‐MFS also exhibits excellent separation performance of a water‐in‐oil emulsion. Furthermore, since the SHpho‐MFS can linearly release protons in an aqueous solution, during the oil/water separation (water‐removing), an aqueous solution of a strong base is neutralized or changed into a certain solution with a tailored pH by a simple filtration step using an appropriately sized SHpho‐MFS. The SHpho‐MFS can maintain a slow reaction rate and reduce the sudden release of heat during neutralization. Controlled release of the SHpho‐MFS capable of the ordered production of protons on demand is also achieved because the release "on and off" behavior of protons is repeatedly observed for every cycle. Abstract : This paper reports a one‐step approach to switching a superhydrophilic sponge to a superhydrophobic sponge with a controlled release characteristic of protons on demand.